Effective methylation triage of HPV positive women with abnormal cytology in a middle‐income country. Issue 6 (24th October 2020) - Ramírez, Arianis Tatiana; Sánchez, Gloria Inés; Nedjai, Belinda; Agudelo, María Cecilia; Brentnall, Adam R.; Cuschieri, Kate; Castañeda, Kelly Melisa; Cuzick, Jack; Lorincz, Attila T.; ,
Abstract: The S5‐methylation test, an alternative to cytology and HPV16/18 genotyping to triage high‐risk HPV‐positive (hrHPV+) women, has not been widely validated in low‐middle‐income countries (LMICs). We compared S5 to HPV16/18 and cytology to detect cervical intraepithelial neoplasia Grade 2 or worse (CIN2+) and CIN3+ in hrHPV+ women selected from a randomized pragmatic trial of 2661 Colombian women with an earlier‐borderline abnormal cytology. We included all hrHPV+ CIN2 and CIN3+ cases (n = 183) age matched to 183 <CIN2 hrHPV+. Baseline specimens were HPV‐genotyped and tested by S5‐methylation, blinded to cytology, histology and initial HPV results. We evaluated the test performance of predefined S5‐classifier (cut‐point 0.8) and a post hoc classifier at a different cut‐point (3.1). S5 sensitivity for CIN2+ was 82% (95% confidence interval [CI] 76.4‐87.5) and for CIN3+ 77.08% (95% CI 65.19‐88.97). S5 sensitivity was higher than HPV16/18 sensitivity (48.1%, 95% CI 40.85‐55.33) or cytology (31.21%, 95% CI 24.50‐37.93) but with lower specificity (35%, 95% CI 28.1‐42). At cut‐point 3.1, S5 sensitivity for CIN2+ (55.2%, 95% CI 48‐62.4) or CIN3+ (64.6%, 95% CI 51.0‐78.1) was also superior to HPV16/18 ( P < .05) or cytology ( P < .0001). At this cut‐point S5 specificity (76%, 95% CI 69.8‐82.1 for <CIN2) was higher than HPV16/18 (67.21%, 95% CI 60.41‐74.01, P = .0062) and similar to cytology (75.57%, 95% CI 69.34‐81.79, P = 1). HPV16/18 plus cytology sensitivity was similar to S5 for CIN3+, however, false‐positive rate was higher (50.27% vs. 24.04%). High sensitivity is crucial in LMICs, S5‐methylation exceeded HPV16/18 or cytology sensitivity with comparable specificity for CIN2+ and CIN3+ in hrHPV‐positive Colombian women. Furthermore, S5 triage had comparable sensitivity and significantly fewer false positives than cytology and HPV16/18 combination. What's new?: For cervical cancer screening, testing HPV16/18 types has lower specificity than cytology, but a high false positive rate. Here, the authors evaluated the S5 classifier test, which is based on DNA methylation. They found that for triaging women who test positive for high risk HPV, S5 had better sensitivity and fewer false positives than cytology plus HPV16/18. This paper represents the first time that S5 methylation has been tested head‐to‐head with cytology and HPV16/18 testing in a LMIC. As affordable methylation tests become available, this strategy may prove useful for triage in low resource settings.